A Rare Cause of Hypercalcemia: Immobilization A Case Report and Literature Review - Gulsah Elbuken; Bahadir Yazicioglu; Onur Ozturk; Mehmet Derya Demirag (Medicine Science, 2015)
Immobilization hypercalcemia (IH) mainly results from rapid bone turnover and may be seen after spinal cord injury or long bone fracture in particular in children and adolescents. The pathophysiology of this entity is entirely unknown. A-19 year-old, male quadriplegic adolescent was referred to our outpatient clinic by a family physician. At presentation he had some vague symptoms due to hypercalcemia including fatigue, nausea, vomiting, anorexia, constipation and dehydration. Laboratory investigations for hypercalcemia revealed low intact parathyroid hormone level, low 25-0H vitamin D, and high 24-hour urine calcium. He was diagnosed as having IH after all other causes of hypercalcemia were excluded. The pathophysiology of IH remains unclear. Treatment is directed towards lowering the serum calcium level. Up to date, intravenous hydration with isotonic saline, furosemide and salmon calcitonin have been the conventional therapies. Other treatment options include bisposphonates (such as etidronate, zoledronate or pamidronate) or, an inhibitor of receptor activator of nuclear factor kappa-B ligand (RANKL), denosumab. IH is a rare cause of hypercalcemia. Physicians should be aware of this condition when seeing patients with restricted physical activity. [Med-Science 2015; 4(3.000): 2521-7]